The impact of long-term mulching cultivation on soil quality, microbial community structure, and fruit quality in “Wanzhou Red Mandarin” citrus orchard - Liu, Yiding; Teng, Yanqi; Zheng, Jie; Khan, Aziz; Li, Xiang; Cui, Junlin; Verma, Krishan K.; Guo, Qigao; Zhu, Kai (Frontiers in Microbiology, 2025)
Mulching, a widely recognized agricultural practice, involves covering the soil surface with organic or inorganic materials to enhance soil properties and optimize growing conditions. This practice has demonstrably positive effects on soil physicochemical and biological properties, leading to reduced evaporation and weed suppression. This study investigated the effects of grass mulching (GV, Vulpia myuros) versus clean tillage (CK) on soil properties, microbial communities, and fruit quality in a red mandarin orchard. Grass mulching significantly enhanced the surface soil nutrients (0–20 cm), alkali-hydrolyzable nitrogen (AN, 105.5%), available phosphorus (AP, 144.4%), available potassium (AK, 102.1%), soil organic matter (SOM, 42.5%), total organic carbon (TOC, 93.1%), and enzyme activities, i.e., alkaline phosphatase (60.1%), urease (39.3%), and soil deep layer (20–40 cm) showing lower but notable improvements of available phosphorus (116.6%), total organic carbon (101.9%), respectively. Grass mulching enhanced the Proteobacteria abundance (soil surface 36 to 39%, & deep 33 to 37%) and altered fungal dominance (surface: unclassified_Agaricomycetes, deep: Mortierella). Beta diversity revealed distinct microbial clustering between treatments. Soil physicochemical properties (alkali-hydrolyzable nitrogen, electrical conductivity and soil organic matter) strongly correlated with unclassified_Micropepsaceae and Agaricomycetes. Grass mulching improved fruit quality, increased vitamin C (24.5%), and decreased pericarp thickness (27.1%), with bacterial communities showing stronger fruit quality correlations than fungi. These results demonstrated that the grass mulching enhances soil fertility, microbial activity and fruit quality, supporting its adoption in sustainable citrus cultivation in the years to come.